Ethnobotany and the loss of traditional knowledge in the 21st century - Ramirez, C.R. (Ethnobotany Research and Applications, 2007)
30 citations (Crossref) [2023-10-31]
Keywords: dept.bio

Fragmentation of colonial ascidians: Differences in reattachment capability among species - Bullard, Stephan; Sedlack, Betsy; Reinhardt, James F; Litty, Carolyn; Gareau, Keith; Whitlatch, Robert B (Journal of Experimental Marine Biology and Ecology, 2007)
31 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/054-171-469-993-130 tex.type: [object Object]
Keywords: Ascidiacea; Ascidians; Asexual; Didemnum sp.; Didemnum sp. A; Dispersal; Fragments; Invasive; Reproduction; asexual reproduction; biological invasion; dept.bio; dispersal; invasive species; settling behavior; substrate; vertebrate

Life history of the northern mayfly Baetis bundyae in Rankin Inlet, Nunavut, Canada, with updates to the list of mayflies of Nunavut - Giberson, Donna J; Burian, Steven K; Shouldice, Michael (Canadian Entomologist, 2007)
Mayflies (Ephemeroptera) were collected from 35 sites (streams and tundra ponds) across southern Nunavut in 2002-2005. Nine mayfly species were previously reported for Nunavut: Acentrella feropagus Alba-Tercedor and McCafferty, Acerpenna pygmaea (Hagen), Baetis bundyae Lehmkuhl, B. flavistriga McDunnough, B. foemina McDunnough, Diphetor hageni (Eaton) (Baetidae), Ephemerella aurivillii (Bengtsson) (Ephemerellidae), Leptophlebia nebulosa (Walker) (Leptophlebiidae), and Metretopus borealis (Eaton) (Metrotopidae). We add 7 species to this list, bringing the total to 16: Ameletus inopinatus Eaton (Ameletidae), Acentrella lapponica Bengtsson, Baetis hudsonicus Ide, B. tricaudatus Dodds, Heptagenia solitaria McDunnough (Heptageniidae), Rhithrogena jejuna Eaton (Heptageniidae), and Parameletus chelifer Bengtsson (Siphlonuridae). Based on numbers collected, the dominant mayfly family was Baetidae. Baetis bundyae was the most common mayfly collected, particularly in coastal areas, where larvae were found in permanent and temporary streams and in small or shallow tundra ponds. Larvae hatched 2-3 weeks after ice-out and developed rapidly in 2.5-4 weeks, emerging as adults by early August. All populations containing larvae that were large enough to sex showed female-biased sex ratios, suggesting parthenogenesis. A combination of freeze-tolerant eggs, good dispersal ability, and probable parthenogenesis is probably responsible for the success of Baetidae across the Arctic. © 2007 Entomological Society of Canada.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/035-294-733-369-347 tex.type: [object Object]
Keywords: Acentrella feropagus; Acentrella lapponica; Acerpenna pygmaea; Ameletidae; Ameletus inopinatus; Baetidae; Baetis bundyae; Baetis hudsonicus; Canada; Diphetor hageni; Ephemerella aurivillii; Ephemerellidae; Ephemeroptera; Heptagenia solitaria; Heptageniidae; Leptophlebia nebulosa; Leptophlebiidae; Metretopus borealis; North America; Nunavut; Parameletus chelifer; Rhithrogena jejuna; Siphlonuridae; dept.bio; life history; mayfly; parthenogenesis

The size of the nucleus increases as yeast cells grow - Jorgensen, Paul; Edgington, Nicholas P; Schneider, Brandt L; Rupes, Ivan; Tyers, Mike; Futcher, Bruce (Molecular Biology of the Cell, 2007)
It is not known how the volume of the cell nucleus is set, nor how the ratio of nuclear volume to cell volume (N/C) is determined. Here, we have measured the size of the nucleus in growing cells of the budding yeast Saccharomyces cerevisiae. Analysis of mutant yeast strains spanning a range of cell sizes revealed that the ratio of average nuclear volume to average cell volume was quite consistent, with nuclear volume being ∼7% that of cell volume. At the single cell level, nuclear and cell size were strongly correlated in growing wild-type cells, as determined by three different microscopic approaches. Even in G1-phase, nuclear volume grew, although it did not grow quite as fast as overall cell volume. DNA content did not appear to have any immediate, direct influence on nuclear size, in that nuclear size did not increase sharply during S-phase. The maintenance of nuclear size did not require continuous growth or ribosome biogenesis, as starvation and rapamycin treatment had little immediate impact on nuclear size. Blocking the nuclear export of new ribosomal subunits, among other proteins and RNAs, with leptomycin B also had no obvious effect on nuclear size. Nuclear expansion must now be factored into conceptual and mathematical models of budding yeast growth and division. These results raise questions as to the unknown force(s) that expand the nucleus as yeast cells grow. © 2007 by The American Society for Cell Biology.
317 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/157-415-132-250-932 tex.type: [object Object]
Keywords: Active Transport; Cell Nucleus; Cell Nucleolus; Cell Nucleus; Cell Size; DNA content; Green Fluorescent Proteins; Karyopherins; Microscopy; Electron; Mutation; Nuclear Localization Signals; Organelle Size; RNA transport; Receptors; Cytoplasmic and Nuclear; Ribosomes; Saccharomyces cerevisiae; Saccharomycetales; article; cell cycle G1 phase; cell division; cell nucleus; cell volume; dept.bio; fungal cell; fungal strain; fungus growth; leptomycin B; mathematical model; mutant; nonhuman; priority journal; protein transport; ribosome subunit; wild type